MARKET INTEREST RATEREACTION TO CHANGE REDISCOUNTRATE (Research Bulletins of the Faculty of Economic Sciences, 2021)
Carried out research work shows that central bank interest rates have a clear im-pact on market interest rates. Strength depending on the interest rate on deposits and interest rate on credits of rediscount rate turned out to bequite strong. The direction ofthe test compound was positive. The bank's margin in the initial period of constant, then began to grow, which can be attributed to the uncertainty as to further the macroe-conomic situation.
Keywords: rediscount rate, the interest rate market, Granger causality, impulse re-sponse function